A synthesis method of open hollow FeCoNiP@CQDs nanotube structure for seawater electrolysis

Through the mixed-etching-phosphate strategy, carbon quantum dot doped doped triple metal phosphate nanotubes, solve the restrictions of precious metal catalysts and freshwater resources in existing electrolytic water technology, realize efficient sea water electrolysis water decomposition, has a having a decomposition of sea water electrolyte water. Excellent electrochemical properties and structural stability.

CN115323428BActive Publication Date: 2025-01-24QINGDAO UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210942742.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-08
Publication Date
2025-01-24
Estimated Expiration
2042-08-08

AI Technical Summary

Technical Problem

Existing electrolytic technology requires expensive precious metal catalysts and scarce freshwater resources, limiting its large-scale commercial development.

Method used

Adopt a strategy of doping-etching-phosphorusization, to prepare an open hollow structured three-metal phosphoricide nanotube with carbon quantum dotted, as high-efficiency electrolytic water catalytic materials.

Benefits of technology

This material shows excellent electrochemical properties, including high ratio surface area, good conductivity and rich active site, which can highly catalyze water decomposition in seawater, and has good structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003786379180000011
    Figure HDA0003786379180000011
  • Figure HDA0003786379180000012
    Figure HDA0003786379180000012
  • Figure HDA0003786379180000013
    Figure HDA0003786379180000013
Patent Text Reader

Abstract

The present invention relates to a synthesis method of an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater: first, carbon quantum dots (CQDs) are added in the process of preparing MIL-88A to prepare a CQDs-doped MIL-88A precursor (MIL-88A@CQDs); then it is dispersed in an ethanol solution, mixed evenly with an aqueous solution of cobalt nitrate hexahydrate, nickel nitrate hexahydrate and urea, and a FeCoNi-LDHs@CQDs nanotube with an open hollow structure is prepared by hydrothermal reaction at 90°C for 5h; then it is placed at both ends of a porcelain boat with sodium hypophosphite (NaH2PO2), and a FeCoNiP@CQDs nanotube with an open hollow structure is prepared by phosphating reaction at 300°C in a tube furnace for 2h. Both the inner and outer surfaces of the open hollow structure can provide active sites, and are conducive to improving the mass transfer rate and the escape of bubbles. At the same time, the phosphorus defects generated during element doping and phosphating are conducive to adjusting the electronic structure, improving the inherent activity of the material, and enhancing the electrocatalytic seawater decomposition performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic water decomposition of functional nanocomposite materials, and specifically, is a synthesis method for preparing an open hollow trimetallic phosphide composite material using an iron-metal organic framework material as a precursor and its application in electrochemical catalytic seawater decomposition. Background Art

[0002] H2 has become an ideal clean energy source for solving energy crises and environmental pollution due to its high energy density and pollution-free combustion. Hydrogen production by water electrolysis is currently the most effective hydrogen production technology. It has a simple operation process and high hydrogen purity. At the same time, it can use renewable energy to achieve "zero carbon" production. At present, industrialized water electrolysis technology requires the use of expensive precious metal catalysts and scarce fresh water resources, which limits the large-scale development of water electrolysis technology. Therefore, how to develop efficient non-precious metal water electrolysis catalyst materials to realize the electrolysis process of seawater, brine and even wastewater is an effective strategy to improve the large-scale commercial use of water electrolysis technology.

[0003] Transition metal phosphides (TMPs) have metal-like conductivity and excellent intrinsic activity and have been widely used in the field of water electrolysis. In order to improve mass transfer and adsorption / desorption of active species, the morphology of TMPs usually needs to be designed to meet the supply of raw materials in the catalytic process and the rapid escape of generated gas components. Although traditional hollow materials can provide higher specific surface area and excellent mass transfer rate, the gas escape rate is low and it is easy to block the active sites. Open hollow materials can not only provide accessible active sites on both the inner and outer surfaces, but also facilitate gas escape. At the same time, element doping can regulate the electronic structure of TMPs and produce abundant defects or lattice distortions, thereby improving the intrinsic activity of the material. Therefore, designing open-structured and heterostructured TMPs, regulating element doping, and optimizing electronic structure and crystal phase are effective strategies for constructing high-performance electrode materials. Summary of the invention

[0004] The present invention proposes a strategy combining doping, etching and phosphating, firstly introducing carbon quantum dots (CQDs) into MIL-88A for doping, and then introducing cations (Co 2+ / Ni 2+ ) is etched in a mixed solution of ethanol and water; at the same time, through a precise and controllable phosphating process, the carbon quantum dot-doped open hollow structure trimetallic phosphide is prepared, which has a high specific surface area, good conductivity and abundant active sites. The prepared electrode materials can be used as anodes and cathodes of electrolytic cells, respectively, with excellent catalytic performance and good structural stability.

[0005] In order to prepare electrolytic water catalytic materials with good catalytic performance, the present invention is based on the MIL-88A precursor, and through a strategy combining doping-etching-phosphating, anode and cathode materials with excellent performance are prepared at the same time. The synthesis of electrode materials can be achieved through the following technical routes:

[0006] 1. A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater, comprising the following steps:

[0007] (1) Preparation of carbon quantum dots (CQDs): Two platinum sheets were used as anode and counter electrode, 150 mL of ethanol containing sodium hydroxide (NaOH) and distilled water (V:V = 14:1) were used as electrolytes, and a dark brown solution was obtained by electrolysis at a certain voltage for 24 to 30 h. Then, the supernatant was centrifuged and 150 mL of ethanol was added to the obtained supernatant to precipitate the NaOH salt. After evaporating the supernatant, a reddish-brown slurry was obtained and further dispersed in 100 mL of deionized water. The prepared suspension was dialyzed for 24 h multiple times to remove residual NaOH and obtain a neutral CQDs solution.

[0008] (2) Preparation of MIL-88A@CQDs precursor: Fumaric acid and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) in a certain molar ratio (1:(1-2)) were dissolved in deionized water respectively, and then the two solutions were heated and mixed, and an oil bath reaction was carried out. A certain amount of carbon quantum dots were added during the oil bath to obtain MIL-88@CQDs precursor. The oil bath temperature was 100-120°C and the oil bath time was 5-7h.

[0009] (3) Preparation of FeCoNi-LDHs@CQDs (FCN-LDHs@CQDs) open hollow nanotubes: First, the MIL-88A@CQDs prepared in (2) were dispersed in an ethanol solution, and then a certain mass ratio of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and urea were dissolved in the aqueous solution. The two solutions were mixed and stirred evenly, and a solvothermal reaction was carried out to obtain FCN-LDHs@CQDs nanotubes. The reaction temperature was 80-100°C and the reaction time was 3-8h.

[0010] (4) Preparation of FeCoNiP-LDHs@CQDs (FCNP@CQDs) open hollow nanotubes: The FCN-LDFs@CQDs nanotubes prepared in (3) and a certain amount of sodium hypophosphite (NaH2PO2) were placed at both ends of a porcelain boat, and heated in a tube furnace under inert gas flow conditions to prepare the target product FCNP@CQDs nanotubes. The heating temperature was 300-500°C and the heating time was 2-4 h.

[0011] The preparation method according to technical route 1 is characterized in that: in the step (1), the amount of NaOH is 1.0 g, the electrolysis voltage is 20 V, the electrolysis time is 24 h, and the concentration of the prepared CQDs is 4 mg / mL.

[0012] The preparation method according to technical route 1 is characterized in that: in the step (2), the molar ratio of fumaric acid to Fe(NO3)3·9H2O is 1:1.08, the optimal amount of carbon quantum dots added is 2 mL, the optimal temperature of the oil bath is 110°C, and the optimal oil bath time is 6 h.

[0013] The preparation method according to technical route 1 is characterized in that: in the step (3), the optimal mass ratio of Co(NO3)2·6H2O, Ni(NO3)2·6H2O and urea is 9:3:8, the optimal volume ratio of ethanol to water is 4:6, the optimal temperature of the solvothermal reaction is 90°C, and the optimal time is 5h.

[0014] The preparation method according to technical route 1 is characterized in that the mass ratio of NaH2PO2 in step (4) to the FCN-LDFs@CQDs nanotubes prepared in step (3) is 12:1.

[0015] The preparation method according to technical route 1 is characterized in that: the FCNP@CQDs nanotubes prepared in step (4) can be used as anode and cathode materials for electrocatalytic seawater decomposition.

[0016] As a further feature of the present invention, the trimetallic phosphide nanotubes (FCNP@CQDs) with an open hollow structure obtained in step (4) have excellent electrochemical performance in catalyzing the decomposition of seawater. The oxygen evolution reaction (OER) test was carried out under a three-electrode system. When the current density reached 20 mA cm -2 When the optimal sample is 2.5×10 Å, the overpotential required is only 268 mV, and the Tafel slope is 45.2 mVdec. -1 , at 20mA cm -2 The 12h constant voltage stability can be maintained at 99.98% under current density test; when the hydrogen evolution reaction (HER) test is carried out, the current density reaches 20mA cm -2 The optimal sample requires only 150 mV overpotential and the Tafel slope is 87 mVdec -1 , at 20mA cm -2 The 12h constant voltage stability test under current density can maintain 99.91%.

[0017] As a further feature of the present invention, the trimetallic phosphide nanotubes (FCNP@CQDs) with an open hollow structure obtained in step (4) are assembled into two electrodes for electrolysis of seawater, and a current of 10 mA cm-2 can be achieved at a voltage of 1.61 V. -2 The current density can maintain 97% stability at a constant current of 50h.

[0018] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0019] The key to the success of the open hollow structure trimetallic phosphide nanotubes based on the MIL-88A@CQDs precursor is the etching of MIL-88A@CQDs. During the heating process, NH3 formed by the decomposition of urea etches MIL-88A to release Fe-NH3 complex ions, which then react with Co 2+ 、Ni 2+ and OH - Co-precipitation forms an LDH shell. With continuous etching, free ions accumulate at the FCN-LDHs interface and gradually self-assemble into FCN-LDHs@CQDs. Finally, the open hollow structure tri-metal FCN-LDHs@CQDs nanotubes are prepared into FCNP@CQDs nanotubes through a controllable phosphating process. The inner and outer surfaces of the open hollow structure can provide active sites, which is beneficial to accelerate mass transfer and the escape of bubbles. The doping of CQDs is beneficial to improve the conductivity of the material. Therefore, the tri-metal phosphide with an open hollow structure prepared by the method of the present invention exhibits excellent electrochemical properties. Specifically, in the OER test, FCNP@CQDs is at 20mA cm -2 The overpotential at the current density of 20 mA cm-1 is 268 mV. In the HER test, FCNP@CQDs -2 The overpotential at a current density of 150 mV. The material was assembled into two electrodes for seawater electrolysis test and showed excellent catalytic performance, reaching 10 mA cm at a voltage of 1.61 V. -2 The current density can be maintained at 97% after 50h stability test. DETAILED DESCRIPTION

[0020] The technical features of the present invention are described below in conjunction with specific experimental schemes and drawings, but the present invention is not limited thereto. The experimental methods described in the following examples are conventional methods unless otherwise specified; the instruments and materials described are commercially available unless otherwise specified.

[0021] Example 1

[0022] A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater comprises the following steps:

[0023] (1) Two platinum sheets (1*1 cm) were used as the anode and counter electrode, respectively. 150 mL of ethanol containing sodium hydroxide (NaOH) and distilled water (V:V=14:1) were used as electrolytes. A dark brown solution was obtained by electrolysis at 20 V for 24 h. Then, the supernatant was centrifuged and 150 mL of ethanol was added to the obtained supernatant to precipitate the NaOH salt. After evaporating the supernatant, a reddish-brown slurry was obtained and further dispersed in 100 mL of deionized water. The prepared suspension was dialyzed for 24 h to remove residual NaOH, and a neutral CQDs solution with a concentration of 4 mg / mL was obtained by multiple dialyses.

[0024] (2) Fumaric acid and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) with a molar ratio of 1:1.08 were dissolved in deionized water, and then the two solutions were heated and mixed. 2 mL of CQDs were added and refluxed in an oil bath at 110 °C for 6 h. After cooling to room temperature, centrifugation and drying were performed. The morphology of the obtained MIL-88A@CQDs is shown in the scanning electron microscopy image ( Figure 1 ), the prepared material has a rod-like morphology.

[0025] (3) The MIL-88A@CQDs precursor prepared in the previous step was dispersed in 4 mL of ethanol solution and transferred to a polytetrafluoroethylene-lined reactor. 6 mL of a mixed aqueous solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O and urea was added. After stirring evenly, the mixture was hydrothermally reacted at 90 °C for 5 h. After cooling to room temperature, the mixture was centrifuged, washed and dried to obtain FCN-LDHs@CQDs. The morphology of FCN-LDHs@CQDs is shown in its scanning electron microscopy image ( Figure 2 ), combined with transmission electron microscopy images ( Figure 3 ) shows that the material forms an open hollow nanotube morphology.

[0026] (4) The FCN-LDHs@CQDs nanotubes prepared in step (3) and 212 mg of NaH2PO2 were placed at both ends of a porcelain boat and heated at 300°C for 2 h in a tube furnace under nitrogen flow to prepare the target product FCNP@CQDs. The morphology of FCNP@CQDs is shown in its scanning electron microscope image ( Figure 4 ), combined with transmission electron microscopy images ( Figure 5 ) It can be seen that the nanotubes after phosphating still maintain an open hollow tubular structure. The results of the mapping test on FCNP@CQDs nanotubes are shown in Figure 6As shown in the figure, the material contains Fe, Co, Ni, C, and P elements, indicating that the phosphating is successful. The EPR test results show that it has abundant phosphorus defects ( Figure 7 ). In the three-electrode system, the OER performance of the material in 1M KOH seawater solution is as follows Figure 8 As shown, when the current density reaches 20 mA cm -2 When the overpotential is only 268mV, the performance of HER is as follows Fig. 9 As shown, when the current density reaches 20 mA cm -2 When the overpotential is only 150mV, it is worth noting that at over 120mA cm -2 Its catalytic performance is better than that of commercial Pt / C materials at high current density. The electrolytic water performance of the material when used as both anode and cathode is shown in Figure 2. Fig.10 As shown, at a current density of 20 mA cm -2 The required potential is 1.61 V. In the 50h stability test, 97% stability can be maintained.

[0027] Example 2

[0028] A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater comprises the following steps:

[0029] (1) The preparation of CQDs solution is the same as in Example 1(1).

[0030] (2) The preparation of MIL-88A@CQDs precursor is the same as in Example 1(2).

[0031] (3) The preparation of FCN-LDHs@CQDs was the same as in Example 1(3). The electrochemical performance of the obtained FCN-LDHs@CQDs was directly tested in a 1M KOH seawater solution under three electrodes. The OER performance of the material was as follows: Fig.11 As shown, it reaches 20mA cm -2 The overpotential of current density (η 20 ) is 288mV; its HER performance is as follows Fig.12 As shown, η 20 =286mV. The performance of the two electrodes for complete water splitting is shown in the figure below. Fig.13 As shown, the current density reaches 10 mA cm -2 The potential is 1.7V.

[0032] Example 3

[0033] A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater comprises the following steps:

[0034] (1) The preparation process of MIL-88A precursor is similar to that of Example 1(2), but this process does not require the addition of CQDs.

[0035] (2) The prepared MIL-88A was subjected to a hydrothermal reaction according to Example 1 (3) to obtain FCN-LDHs. The morphology of FCN-LDHs is shown in its scanning electron microscopy image ( Fig.14 ).

[0036] (3) The obtained FCN-LDHs product is phosphated, similar to Example 1 (4), to obtain FCNP. The morphology of FCNP is shown in its scanning electron microscopy image ( Fig.15 The prepared FCNPs were subjected to electrochemical performance tests in a 1 M KOH seawater solution under a three-electrode system, and their OER performance was shown in Figure 2. Fig.16 As shown, η 20 =281mV; HER performance is as follows Fig.17 As shown, η 20 =195mV.

[0037] Example 4

[0038] A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater comprises the following steps:

[0039] (1) The preparation of CQDs solution is the same as in Example 1(1).

[0040] (2) The preparation of MIL-88A@CQDs precursor is the same as in Example 1(2).

[0041] (3) The preparation of FN-LDHs@CQDs was similar to that of Example 1(3), but Co(NO3)2·6H2O was not added during this process.

[0042] (4) The phosphating process is similar to that of Example 1 (4), except that FCN-LDHs@CQDs is replaced with FN-LDHs@CQDs to obtain the product FNP-LDHs@CQDs. The morphology of FNP@CQDs is shown in its scanning electron microscopy image ( Fig.18 ), which are nanorods assembled from nanosheets.

[0043] Example 5

[0044] A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater comprises the following steps:

[0045] (1) The preparation of CQDs solution is the same as in Example 1(1).

[0046] (2) The preparation of MIL-88A@CQDs precursor is the same as in Example 1(2).

[0047] (3) The preparation of FC-LDHs@CQDs was similar to that of Example 1(3), but Ni(NO3)2·6H2O was not added during this process.

[0048] (4) The phosphating process is similar to that of Example 1 (4), except that FCN-LDHs@CQDs is replaced with FC-LDHs@CQDs to obtain the product FCP@CQDs. The morphology of the obtained FCP@CQDs is shown in its scanning electron microscopy image ( Fig.19 ).

[0049] The description of the embodiments disclosed in the present invention is not intended to limit the scope of the present invention, but is used to describe the present invention. Accordingly, the scope of the present invention is not limited by the above embodiments, but is defined by the claims or their equivalents. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 : Scanning electron microscopy image of MIL-88A@CQDs obtained in Example 1;

[0051] Figure 2 : Scanning electron microscopy image of FCN-LDHs@CQDs obtained in Example 1;

[0052] Figure 3 : Transmission electron microscopy image of FCN-LDHs@CQDs obtained in Example 1;

[0053] Figure 4 : Scanning electron microscopy image of FCNP@CQDs obtained in Example 1;

[0054] Figure 5 : Transmission electron microscopy image of FCNP@CQDs obtained in Example 1;

[0055] Figure 6 : Mapping diagram of FCNP@CQDs obtained in Example 1;

[0056] Figure 7 : EPR image of FCNP@CQDs obtained in Example 1;

[0057] Figure 8 : OER performance diagram of FCNP@CQDs obtained in Example 1;

[0058] Fig. 9 : HER performance diagram of FCNP@CQDs obtained in Example 1;

[0059] Fig.10: Full water decomposition performance diagram of FCNP@CQDs obtained in Example 1;

[0060] Fig.11 : OER performance diagram of FCN-LDHs@CQDs obtained in Example 2;

[0061] Fig.12 : HER performance diagram of FCN-LDHs@CQDs obtained in Example 2;

[0062] Fig.13 : Full water splitting performance diagram of FCN-LDHs@CQDs obtained in Example 2;

[0063] Fig.14 : Scanning electron microscopy image of FCN-LDHs obtained in Example 3;

[0064] Fig.15 : Scanning electron microscopy image of FCNPs obtained in Example 3;

[0065] Fig.16 : OER performance diagram of FCNPs obtained in Example 3;

[0066] Fig.17 : HER performance diagram of FCNPs obtained in Example 3;

[0067] Fig.18 : Scanning electron microscopy image of FNP@CQDs obtained in Example 4;

[0068] Fig.19 : Scanning electron microscope image of FCP@CQDs obtained in Example 5.

Claims

1. A method for synthesizing an open hollow FeCoNiP@CQDs nanotube structure for electrolysis of seawater, comprising the following steps: (1) Preparation of carbon quantum dots CQDs: Two platinum sheets were used as the anode and counter electrode, and 150 mL of ethanol and distilled water containing sodium hydroxide were used as electrolytes with a volume ratio of V 乙醇 :V 水 =14:1, a dark brown solution was obtained by electrolysis at a certain voltage for 24 to 30 hours; then, the supernatant was centrifuged and 150 mL of ethanol was added to the obtained supernatant to precipitate the NaOH salt; after evaporating the supernatant, a reddish brown slurry was obtained and further dispersed in 100 mL of deionized water; the prepared suspension was dialyzed for 24 hours multiple times to remove the residual NaOH and obtain a neutral CQDs solution; (2) Preparation of MIL-88A@CQDs precursor: Fumaric acid and ferric nitrate nonahydrate in a molar ratio of 1:1 to 2 were dissolved in deionized water, and then the two solutions were heated and mixed, and an oil bath reaction was performed. A certain amount of carbon quantum dots were added during the oil bath to obtain MIL-88@CQDs precursor. The oil bath temperature was 100 to 120 °C and the oil bath time was 5 to 7 h. (3) Preparation of FCN-LDHs@CQDs open hollow nanotubes: First, the MIL-88A@CQDs prepared in (2) were dispersed in an ethanol solution, and then a certain mass ratio of cobalt nitrate hexahydrate, nickel nitrate hexahydrate and urea were dissolved in the aqueous solution, and the two solutions were mixed and stirred evenly, and a solvothermal reaction was carried out to obtain FCN-LDHs@CQDs nanotubes. The reaction temperature was 80-100°C and the reaction time was 3-8h. (4) Preparation of FCNP@CQDs open hollow nanotubes: The FCN-LDFs@CQDs nanotubes prepared in (3) and a certain amount of sodium hypophosphite were placed at both ends of a porcelain boat, and heated in a tube furnace under inert gas flow conditions to prepare the target product FCNP@CQDs nanotubes. The heating temperature was 300-500°C and the heating time was 2-4 h.

2. The synthesis method according to claim 1, characterized in that: In the step (2), the molar ratio of fumaric acid to ferric nitrate nonahydrate is 1:1.08, and the amount of carbon quantum dots added is 1-3 mL.

3. The synthesis method according to claim 1, characterized in that: The mass ratio of the cobalt nitrate hexahydrate, nickel nitrate hexahydrate and urea in the step (3) is 6 to 12:3:

8.

4. The synthesis method according to claim 1, characterized in that: The FCNP@CQDs prepared in step (4) can be used as anode and cathode materials of an electrolytic cell for electrolysis of seawater.

Citation Information

Patent Citations

  • Preparation method and application of carbon quantum dot / metal organic skeleton catalyst

    CN107754861A

  • Bio-based carbon material loaded inorganic matter composite electrocatalyst and preparation method thereof

    CN112481638A